Pengaruh Tehnik Relaksasi Benson terhadap Nyeri dan Tingkat Kecemasan pada Pasien yang Menjalani Kemoterapi - Yuna Ernawati; Dwi Retno Sulistyaningsih; Erna Melastuti (An-Najat, 2025)
Patients undergoing chemotherapy often face side effects such as pain and anxiety, which may negatively impact their quality of life and adherence to treatment. While pharmacological management is commonly used, non-pharmacological interventions such as relaxation techniques are increasingly being considered to complement conventional therapy. This study aimed to examine the effect of the Benson relaxation technique on pain and anxiety levels in patients undergoing chemotherapy. A quasi-experimental design with a pretest-posttest control group was employed, and purposive sampling was used to recruit 70 respondents who met the inclusion criteria. Pain intensity was measured using the Numerical Rating Scale (NRS), and anxiety levels were assessed using the Zung Self-Rating Anxiety Scale (ZSAS). Data were analyzed using the Marginal Homogeneity test. The results demonstrated a significant reduction in both pain (p = 0.000) and anxiety (p = 0.000) in the intervention group after the implementation of the Benson relaxation technique, while no significant changes were observed in the control group. These findings indicate that the Benson relaxation technique is effective in reducing pain and anxiety among patients receiving chemotherapy. The study highlights the importance of integrating simple, low-cost, and non-invasive interventions into oncology nursing care. Furthermore, the Benson relaxation technique can be recommended as a supportive therapy to improve patient comfort, psychological well-being, and treatment adherence in chemotherapy settings.